Shortage of generic neurologic therapeutics: An escalating threat to patient care. (12th December 2017) - Omorodion, Jacklyn O.; Algahtani, Rami M.; Zocchi, Mark S.; Fox, Erin R.; Pines, Jesse M.; Kaminski, Henry J.
Abstract : Objective: To assess longitudinal trends in shortages of generic drugs used for neurologic conditions over a 15-year period in the United States. Methods: Drug shortage data from the University of Utah Drug Information Service (UUDIS) from 2001 to 2015 were analyzed. Medications were included that were likely to be prescribed by a neurologist to treat a primary neurologic condition or critical for care of a patient with a neurologic condition. Trends in shortage length were assessed using standard descriptive statistics. Results: A total of 2, 081 shortages were reported by UUDIS and 311 (15%) involved medications for neurologic conditions. After excluding discontinued products, 291 shortages were analyzed. The median number of neurologic drugs in shortage was 21 per month with a median duration of 7.4 months. During the three 5-year periods of 2001–2005, 2006–2010, and 2011–2015, a median of 12.5, 14, and 45 drugs were in shortage, respectively. A maximum of 50 drugs in shortage was reached in December 2012 and December 2014. By the end of the study period, 30 neurologic drugs remained in shortage. In over half of the shortages, manufacturers did not provide a reason for the shortage. When reported, manufacturing delays, followed by supply/demand issues, raw material shortages, regulatory issues, and business decisions were cited. Conclusions: Continued drug shortages may compromise the care of patients with neurologic conditions. Manufacturers, together with professional organizations, patient advocacy groups, and the government, need to continue to address this issue, which may escalate with a growing burden of neurologic disease.